Mangrove dynamics driven by Late Holocene drought at Laguna Bacalar, Mexico - A.A. Aragón-Moreno; G.A. Islebe; N. Torrescano-Valle; H.A. Hernández-Arana; A. Carrillo-Bastos; R. Friedel (Quaternary Environments and Humans)
Laguna Bacalar, one of Mexico's most significant near-coast lakes, remains underexplored in the context of its Late Holocene paleoecology. A 2,40 m long core was retrieved in northern Laguna Bacalar. Palynological and geochemical proxies were isolated and analyzed. Our findings reveal the intricate paleoecological dynamics and hydrodynamic shifts of this vital area in southeastern Mexico. Climate and ecological changes delineate three pivotal phases during the Late Holocene at Laguna Bacalar: (i) a period between 3600 and 3250 cal BP mirroring current climatic conditions with seasonal dry tropical forest and mangroves as the dominant vegetation and evidence of human activities indicated by the presence of fossil maize pollen, (ii) a relatively arid phase from 3250 to 2600 cal BP, influenced by heightened ENSO-driven precipitation variability and sea level rise favoring an estuarine environment at Laguna Bacalar, and (iii) a period between 2600 and 2200 cal BP, exhibiting hydrological conditions akin to contemporary conditions with wetland forest mangrove vegetation. These data ultimately underscore the region's susceptibility to regional climatic fluctuations and ecological resilience, providing a case study from which to predict future conditions and establish modern conservation policy for Laguna Bacalar and similar environments.